The Gaze Scenes. - Dimitrijevic, Branislav; Sretenovic, Dejan (Beograd : Paviljon Veljkovic - Cinema Rex - Beograd : Soros Center For Contemporary Arts, 1995)
Cekic, Jovan ; Joksimovic, Zdravko ; Kacic, Darija ; Milivojevic, Era ; Naskovski, Zoran ; Pantelic, Apsolutno Zoran ; Paripovic, Nesa ; Szombathy, Bálint ; Andelkovic, Dejan ; Davic, Aleksandar ; Kocic, Nina ; Markovic, Sasa ; Kadovanovic, Jelica ; Sijak, Ivan ; Talent
biografie
Engels
boek